Preventive Criminal Regulation on the Risk of Crime by Artificial Intelligence in Indonesia - Hendri Khuan (PT. Anagata Sembagi Education, 2025)
The rapid development of Artificial Intelligence (AI) technology has presented new legal challenges, especially in the realm of criminal law in Indonesia. AI systems that are capable of acting autonomously create the potential for digital crime that cannot be reached by conventional criminal law structures that are oriented towards human offenders. The Criminal Code and Law No. 19 of 2016 concerning Information and Electronic Transactions are still human-centric and have not anticipated crimes mediated by non-human entities. This study uses normative juridical methods to evaluate the normative gaps in criminal regulation against AI-based crimes and offers a risk-based preventive criminal regulation model. This approach emphasizes the importance of a legal system that is adaptive to the design and implementation of AI from the early stages, by adopting the principles of risk-based regulation and precautionary principles. The regulations formulated must not only ensure legal accountability for potential violations, but also uphold ethical and human rights values. The recommendations include the need to redefine legal subjects, strengthen institutional capacity, and establish new laws on AI. Thus, risk-based criminal law reform is a juridical urgency in building a national legal system that is responsive to the threat of autonomous technology in the digital era.